At-TaTanāwub, At-TaTaqdīm WaWa At-TaTa’khīr, dan Al-Iltifāt (Kajian Stilistika al-Qur’an dan Puisi Arab) - Achmad Khusnul Khitam (Mukaddimah: Jurnal Studi Islam, 2018)
The discussion of the secrets lies behind the Arabic language or, in particular, in the Qur’an has been a popular for recent years. There are dozens of works which deals with any aspects of the Qur’an, or Arabic language in general, from its grammar, meaning, I’jaz, and any other aspects. One aspect that is attracted many attentions among linguists in particular, is the style of language in the Qur’an, or in Arabic language in general. This paper aims to discuss such matter, especially to elaborate some prominent theories in stylistcs, which are at-tānawub, at-taqdīm wa at-ta’khīr, and iltifāt. There are two consecutive subjects in which the researcher would apply the theories, the language of the al-Qur’an and Arabic poetry. This paper is condered as a library research; a research that is proceed by gathering some books, articles, and other related sources. This paper would be approached by using two appropriate approaches, which are stylistics’ and semantics’ approach. From this research, it is found that each of styles which are used by Qur’an and Arabic poetry have very certain meanings occur behind those styles, which, in some extent, differentiate from their ‘surface’ meanings.